Role of expression of host cytokines in the pathogenesis of H9N2-PB2 reassortant and non-reassortant H5N1 avian influenza viruses isolated from crows in BALB/c mice. (December 2021) - Kombiah, Subbiah; Kumar, Manoj; Murugkar, Harshad Vinayakrao; Nagarajan, Shanmugasundaram; Tosh, Chakradhar; Senthilkumar, Dhanapal; Rajukumar, Katherukamem; Kalaiyarasu, Semmannan; Gautam, Siddharth; Singh, Rajendra; Karikalan, Mathesh; Sharma, Anil Kumar; et al.
Abstract: The present experiment was conducted to study the role of cytokine, chemokine and TLRs responses of H9N2-PB2 reassortant H5N1 virus as compared to non-reassortant H5N1 virus isolated from crows in BALB/c mice. Two groups (12 mice each) of 6–8 weeks old BALB/c mice were intranasally inoculated with 10 6 EID50 /ml of viruses A/crow/India/03CA04/2015 (H9N2-PB2 reassortant H5N1) and A/crow/India/02CA01/2012 (non-reassortant H5N1). At each interval, brain, lung and spleen were collected and relative quantification of cytokines, chemokines and TLRs was done by qPCR. The H9N2-PB2 reassortant H5N1 infected mice brain, the transcripts of TLR7 were significantly higher than other cytokines at 3dpi and KC was significantly upregulated at 7dpi. In non-reassortant H5N1 infected mice brain showed, TLR 7 and IFNα upregulation at 3dpi and IFNγ and TLR7 upregulation at 7dpi. The H9N2-PB2 reassortant H5N1 infected mice lung revealed, IL2 and TLR7 significant upregulation at 3dpi and in non-reassortant H5N1 infected mice, IL6 was significantly upregulated. At 7dpi in H9N2-PB2 reassortant H5N1 virus infected group mice, IL1 and TLR 3 were significantly upregulated in lungs and in non-reassortant group mice, IL1 and TLR7 were significantly upregulated. At 3dpi in H9N2-PB2 reassortant H5N1 virus infected mice spleen, IL4, IFNα, IFNβ were significantly downregulated and TLR7 transcript was significantly upregulated. In non-reassortant group mice, IL6, IFNα, IFNβ and TLR 3 were significantly upregulated. At 7dpi in H9N2-PB2 reassortant H5N1 virus infected mice spleen, IFNα, IFNβ and TLR7 were significantly lower than other cytokines and in non-reassortant group mice, IFNα and IFNβ were significantly downregulated. This study concludes that dysregulation of cytokines in lungs and brain might have contributed to the pathogenesis of both the viruses in mice. Highlights: Tissue damage in lungs and brain of H5N1 virus infected mice might be due to elevated levels of pro-inflammatory cytokines. Proinflammatory cytokines (IL1, IL6&KC) and TLRs (3&7) upregulated in brain and lungs of reassortant H5N1 virus infected mice. Cytokine responses in non-reassortant H5N1 virus infected mice less pronounced than in reassortant H5N1 virus infected mice.